AMBRA1: When autophagy meets cell proliferation - Cianfanelli, Valentina (Autophagy, 2015)
A growing amount of evidence reported in the literature in recent years strongly supports the relevance of the interplay between autophagy and other pathways. In this context, the study of the link between autophagy and cell proliferation regulation has been among the most challenging. In our recent publications, we finely characterize a role for the pro-autophagic protein AMBRA1 in the regulation of cell proliferation. AMBRA1 modulates autophagy and interacts with PPP2/PP2A (protein phosphatase 2), thus also modulating MYC protein levels and the cell proliferation rate. Interestingly, this pathway of regulation is controlled by the master regulator of autophagy and cell growth, MTORC1. Notably, in our study we demonstrate the relevance of the AMBRA1-mediated regulation of MYC in tumorigenesis, also identifying AMBRA1 as a tumor suppressor gene.